The negotiation scorecard: a planning tool in business and industrial marketing. Issue 4 (2nd May 2017) - Fleming, David E.; Hawes, Jon M.
Abstract : Purpose: Given the ever-increasing complexity of business-to-business exchange, success is contingent on being able to adapt to any given situation. However, there is little in the way of guidance for how to adapt when it comes to negotiations. This paper aims to help business and industrial marketing professionals "get it right" by introducing a new tool which can be used to determine the appropriateness of using a distributive or an integrative approach for a given negotiation interaction. Design/methodology/approach: To develop this tool, the authors identify key situational factors in the negotiating context that serve as indicators of the appropriate orientation (integrative or distributive) that should be applied based on the extant negotiation literature. From this, they develop a framework to guide negotiators in their selection of an orientation for a particular interaction to achieve the best possible outcome. Findings: The tool developed from the literature review and termed the "Negotiation Scorecard" enables business-to-business marketers to better gauge the negotiation context and develop an interaction style consistent with that situation. This can lead to better deals and/or enhanced long-term relationships within business and industrial marketing channels. Originality/value: This tool is the first of its kind to provide negotiators with a structured and quantifiable metric to guide their planning for future negotiation interactions and offers proscriptive guidance as to the types of strategies and tactics they should plan to use and that they should expect to encounter.